Exchange Sort and Selection Sort Algorithms: Comparison and Theoretical Analysis - Putra, Tri Dharma; Purnomo, Rakhmat (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
The purpose of this study is to analyze the comparison of sorting algorithms. Searching algorithm is a main issue in computer science. Many algorithms have been presented by experts. The main issue is the efficiency of these algorithms. Sorting a large number of data will create time issues. Time needed to sort the data is very crucial in this context. Many sorting algorithms are in the field. Two of them are selection sort and exchange sort algorithms. These two are a popular algorithm in data structure. Exchange sort algorithm is very similar to Bubble Sort. Many say Bubble Sort is the same as Exchange Sort. The difference is in how it compares elements. Exchange sort compares one element to the other elements in the array and swaps elements if necessary. Selection sort algorithm is a combination of sorting and searching. For each process, comparison and theoretical analysis is given. The unsorted elements with the smallest or largest values are searched for and exchanged to their appropriate positions within the array. In the comparison and theoretical analysis 1, it was conducted by hand and we got the numbers to be descending from 11, 23, 30, 39, 41, 51 to be 51, 41, 39, 30, 23, 11. For the comparison and theoretical analysis 2, we got the numbers to be descending from  1, 22, 10, 9, 42, 26 to be 42, 26, 22, 10, 9, 1. The most swap happened in exchange sort of comparison and theoretical analysis 1 with 14 swaps, in the second exchange sort it is only 11 swaps. The research gap is about stages of processes algorithm with methodology systematic literature review. The stages of systematic literature review is presented which is planning, conducting literature search, and reporting. PRISMA flow chart is also presented. a visual representation of the article selection process. This diagram illustrates four main stages: Identification, Screening, Eligibility, Inclusion.